Analisis Sistem Rantai Pasok Minyak - Fajri Harisnanda; Ikhlashia Amaly; Alan Mario Gusman; Fulti Febriani; Alwedria Zamer; Wina Elisya (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2012)
PT Pertamina is a large company engaged in oil business, non-fuel, gas, petrochemicals and lubricants both in Indonesia and outside Indonesia. Therefore, special attention should be given to the supply chain system that applied this company, because taking into consideration the supply chain, companies can ensure that the resulting product in good condition, transported properly, and ensure that the resulting product arrives in the hands of consumers by the state good also. Moreover, taking into consideration the supply chain, companies can also improve the efficiency and productivity of the enterprise and can increase customer confidence in the company.Keywords: supply chain, efficiency, productivity, distribution